Про інноваційне забезпечення інтеграційних процесів у промисловості - Лях, І.І. (Економіка промисловості, 2013)
Викладено основні проблеми української промисловості в контексті інноваційного забезпечення процесів інтеграції. Обґрунтовано, що формування ефективної системи виробництва і застосування знань передбачає якісну інфраструктурну підтримку створення, просування і розповсюдження інноваційного продукту на основі узгодженої, збалансованої інноваційної політики.
Ключові слова: інновація, регулювання, інтеграція, промисловість. Изложены основные проблемы украинской промышленности в контексте инновационного обеспечения процессов интеграции. Обосновано, что формирование эффективной системы производства и применение знаний предусматривает качественную инфраструктурную поддержку создания, продвижения и распространения инновационного продукта на основе согласованной, сбалансированной инновационной политики.
Ключевые слова: инновация, регулирование, интеграция, промышленность. The basic problems of Ukrainian industry in the context of innovation providing of integration processes are given. It is proved that the formation of efficient system of production and use of knowledge presuppose the quality infrastructure support for creation, promotion and distribution of innovation product on the basis of new, coherent, and balanced innovation policy. It is shown that for the improvement of the organizational structure of innovation process towards strengthening the relationship between research, innovation and industrial component that can respond to the needs of production and today's market an effective motivational adjusters are needed.
Keywords: innovation, adjusting, integration, industry.